Vietnam universities: strengthening research and innovation - Phuong, Nguyen Thi; Thu Thuy, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
In the actual context of the world’s economy, the explosion of inter-discipline sectors as well as the essential diversity of higher education show more the important role of fundamental research to development of science, technology and innovation (STI) as a move to build the knowledge based economy for every nation. As for purpose to assess capacities to meet this role of higher education in Vietnam, this paper provides an analysis of the roles of universities in strengthening fundamental research of our country. Code: 16031602